2020
DOI: 10.3390/agronomy10010094
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Medicago sativa Grown in Clay Soil Favored by Compost or Farmyard Manure to Mitigate Salt Stress

Abstract: The use of saline water for the irrigation of forage crops to alleviate water scarcity has become necessary in semi-arid and arid regions and researchers have been seeking ways to offset the harmful results of soil salinity. Soil amendments with compost, manure and other organic material provide a valuable source of plant nutrients and appear to speed up soil recovery. The aim of this study was to compare the benefits of farmyard manure and a municipal solid waste (MSW) compost (40 mg ha−1) for raising alfalfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 68 publications
2
17
1
Order By: Relevance
“…The use of organic sorbents as remediative agents in soil has been questioned due to claims that they could be sources of contaminants including HMs. However, unlike other studies (Hamid et al 2018;Mbarki et al 2020) which found high HM concentrations in some organic sorbents (up to 5.7 mg kg −1 Cd, 12.9 mg kg −1 Pb and 116 mg kg −1 Zn), their contents in the sorbents used in this study were much lower and within acceptable range for use in soil systems (Barth et al 2008). Figures 1, 2 and 3 show the EDTA-extractable fractions of Cd, Pb and Zn, respectively, from soils contaminated with a mixture of HMs spiked into soil at three doses.…”
Section: Immobilisation Of Hms By Organic Sorbentscontrasting
confidence: 89%
“…The use of organic sorbents as remediative agents in soil has been questioned due to claims that they could be sources of contaminants including HMs. However, unlike other studies (Hamid et al 2018;Mbarki et al 2020) which found high HM concentrations in some organic sorbents (up to 5.7 mg kg −1 Cd, 12.9 mg kg −1 Pb and 116 mg kg −1 Zn), their contents in the sorbents used in this study were much lower and within acceptable range for use in soil systems (Barth et al 2008). Figures 1, 2 and 3 show the EDTA-extractable fractions of Cd, Pb and Zn, respectively, from soils contaminated with a mixture of HMs spiked into soil at three doses.…”
Section: Immobilisation Of Hms By Organic Sorbentscontrasting
confidence: 89%
“…So far, Ca 2+ is supposed to be the hub of secondary messengers via Ca 2+ spiking in the nuclear region of root hairs [57]. Compost is rich in several mineral elements including N, P, K + , and Ca 2+ , and it maintains the soil pH [7]. Compost amendment increased the biomass and yield by increasing the uptake of essential mineral elements in crops [58].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high biomass production, high nutritional quality, high protein content, and its perennial growth, alfalfa is becoming more reliable and a great potential species as feedstock for animal and as a sustainable crop for second-generation bioethanol production [5,6]. Alfalfa is widely cultivated in arid and semi-arid areas where salinity is one of the main factors limiting the growth of this crop [7,8], and it strongly contributes to the socio-economic development of the local community [4]. Alfalfa is considered as moderately tolerant to salt and shows a clear stunting and evident yield reduction when the salinity value approaches 20 mM NaCl [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations